2020
DOI: 10.1155/2020/8039671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Zoledronic Acid Administration on Pain Intensity after Percutaneous Vertebroplasty for Osteoporotic Vertebral Compression Fractures

Abstract: Introduction. This study aimed to compare and analyze the effect of preoperative zoledronic acid (ZOL) administration on pain intensity after percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fracture (OVCF). Methods. The study included 242 patients with OVCFs who underwent PVP in our hospital between January 2015 and June 2018. The patients were randomly assigned to either a ZOL group (n = 121) or a control group (n = 121). The patients in the ZOL group were treated preoperatively with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…In addition, the trends for the indexes persisted at 12 months, indicating the stable and durable effect of the ZA injection. Hu et al revealed that ZA treatment exerted a good inhibitory effect after 12 months [32]. Notably, 2 studies performed follow-up of the radiological results, and no significant differences were detected in the Cobb angle and VBH at 12 mo after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the trends for the indexes persisted at 12 months, indicating the stable and durable effect of the ZA injection. Hu et al revealed that ZA treatment exerted a good inhibitory effect after 12 months [32]. Notably, 2 studies performed follow-up of the radiological results, and no significant differences were detected in the Cobb angle and VBH at 12 mo after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism by which PKP/PVP reduces pain remains unclear [ 28 ]. Nevertheless, a few compelling mechanisms have been proposed: heat caused by bone cement could cauterize nerve endings [ 29 ] and stabilize vertebral bodies [ 30 , 31 ], resulting in peripheral nerve ischemia and necrosis by embolizing blood vessels [ 32 ]. Despite the doubts of a correlation between pain relief and radiological outcomes, several studies confirmed the efficacy in the early stage [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As all we known, zoledronic acid could inhabit osteoclasts differentiate and proliferate, regulate bone metabolism and reduce bone loss. In this article, 6 retrospective studies [32][33][34][35][36][37] and 2 prospective studies [38,39]were searched out. 7 studies [32][33][34][35][37][38][39] reported the effect of ZOL and one study [37] reported the effect of Teriparatide.1416 cases, 574 cases in test group and 842 cases in control group, who had residual pain in back or low back were observed.…”
Section: Improving Osteoporosismentioning
confidence: 99%
“…ZOL was used on the second or third day after surgery in the above studies. Hu W et al [34]reported a controlled study of 121 OVCF patients were injected with ZOL before PVP surgery. The results showed that patients in the test group had lower pain scores after one year of followup.…”
Section: Improving Osteoporosismentioning
confidence: 99%